Heterologous Expression Of Violacein Biosynthetic Gene Cluster From Chromobacterium Violaceum Strain Mth01 In Escherichia Coli - Matthew Minggu, Matthlessa (2017)
Violacein, a bisindole pigment produced by Chromobacterium violaceum has tremendous pharmaceutical potential such as antimicrobial, antiparasites and antiviral. The violacein structure is dimeric composed of three structural units, a 5- hydroxyindole, oxindole and 2- pyyrolidone subunits formed by the condensation of two modified tryptophan molecules. Violacein is made by a series of five specific genes termed vzoA, vzoB, vioC, vioE), and vzoE, giving its total sequence length of 7.3 kilo-bases (kb) in size. The present work describes the development of a genetic system for heterologous production of violacein in Escherichia coli cells. C. violaceum strain MTH01, a natural violacein producing bacterium was isolated from the limnological areas of Tasik Harapan at Universiti Sains Malaysia, Pulau Pinang. The complete violacein biosynthetic gene cluster was successfully amplified from MTH01 genomic DNA using violacein gene specific primers, and cloned into pUC19 vector. Sequence analysis of the DNA insert harboured by the recombinant pUC19 clone, pVio!9, showed that the cloned fragment shared 99% homology to published sequences of the C. violaceum violacein biosynthetic gene cluster. The sequenced fragment was subcloned into pET-3a and pET-1 lb expression vectors, yielding recombinant vectors, pVio3a and pViollb, respectively.